2017
DOI: 10.21149/7706
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de los alimentos publicitados entre la audiencia infantil en la televisión chilena

Abstract: Objetivo. Examinar la publicidad de alimentos dirigida a la audiencia infantil en la televisión chilena. Material y métodos. Estudio de diseño transversal. Se registró la publicidad de alimentos emitida por cuatro canales de televisión de señal abierta, durante 12 horas diarias, en 12 días seleccionados aleatoriamente. Los avisos se clasificaron según grupos de alimentos y nivel de procesamiento. Se comparó la frecuencia de avisos de alimentos dirigidos a la audiencia infantil con los destinados a adultos. Se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
1
0
6
Order By: Relevance
“…Dairy-based beverages and meat products were also prevalent. Our finding regarding sweetened beverages corroborates recent studies in Chile and elsewhere ( 9 , 13 ) , and our finding with respect to dairy corroborates an additional study showing that, in Chile, dairy-based products are relevant in food advertising ( 36 ) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Dairy-based beverages and meat products were also prevalent. Our finding regarding sweetened beverages corroborates recent studies in Chile and elsewhere ( 9 , 13 ) , and our finding with respect to dairy corroborates an additional study showing that, in Chile, dairy-based products are relevant in food advertising ( 36 ) .…”
Section: Discussionsupporting
confidence: 92%
“…In Chile, according to a 2007 study, 34 % of the advertising time in child-targeted programmes was dedicated to foods and beverages ( 35 ) . In addition, another recent investigation found that 53 % of food advertising was targeted to children and mostly focused on sugary dairy products (28 %), sweetened beverages (26 %) and breakfast cereals (18 %) ( 36 ) . Most of these studies focus on children’s programming, yet a large proportion of children also watch general-audience programmes, even at night ( 37 ) .…”
mentioning
confidence: 99%
“…-NO DEBE SER ABUSIVA: que incentiva la discriminación, la violencia o vulnera los derechos de los niños, la salud y la seguridad de las personas. 29,30,31 El Código de Defensa del Consumidor define qué es publicidad engañosa y abusiva y provee las penalidades a quien incurre en esas prácticas.…”
Section: Publicidad Televisiva En Edad Escolarunclassified
“…Los niños y niñas se consideran vulnerables y necesitan ser protegidos de las prácticas publicitarias. 29,30,31 Las campañas publicitarias tienen diferentes objetivos, como aumentar el consumo de un producto, insertar una marca o producto en el mercado, posicionar la imagen de una marca, generar recordación en la mente del consumidor de una marca, etc. 29,30 En la actualidad, la publicidad tiene como herramientas muchas otras áreas de conocimiento, como la comunicación social, la psicología, la sociología, la antropología, la estadística o la economía para entender la mejor forma de comunicar un mensaje publicitario y medir los resultados obtenidos.…”
Section: Publicidad Televisiva En Edad Escolarunclassified
See 1 more Smart Citation